A novel synthesis of YVO4:Ln3+ (Ln = Eu, Sm, and Dy) porous/hollow submicro-ellipsoids and their luminescence properties. Issue 19 (30th April 2020) - Zhao, Shuang; Shao, Baiqi; Feng, Yang; Yuan, Senwen; Dong, Langping; Zhang, Liang; You, Hongpeng
Abstract : A novel synthesis strategy of porous/hollow YVO4 submicro-ellipsoids with multicolor emissions has been developed based on the high structural matching of LYH and YVO4 . Abstract : The facile and green synthesis of novel structured inorganic micro/nanocrystals is prospective in the field of functional materials. Herein, uniform porous/hollow YVO4 submicro-ellipsoids were developed via a surfactant-free and one-pot aqueous-based strategy using Y2 (OH)5 NO3 · n H2 O (LYH) as a precursor. We propose a possible morphological evolution mechanism related to quick assembly, followed by the Ostwald ripening process based on a series of time-dependent investigations. Besides, we propose a possible transformation process from LYH to YVO4 on the basis of the high structural matching between [001]LYH and [110]YVO4 . Furthermore, we found that the successful synthesis of porous/hollow YVO4 ellipsoids remarkably depended on the precise tuning of the reaction parameters (reaction temperature, pH value, and Na + concentration). In addition, multicolor down-conversion emissions were realized via lanthanide ion (Ln 3+ : Eu 3+, Sm 3+, and Dy 3+ ) doping. The as-synthesized porous/hollow products may be ideal candidates for bio-/energy-related applications.